Walker 256 Tumor Growth Suppression by Crotoxin Involves Formyl Peptide Receptors and Lipoxin A4 - Patrícia Brigatte; Odair Jorge Faiad; Roberta Cornélio Ferreira Nocelli; Richardt G. Landgraf; Mario Sergio Palma; Yara Cury; Rui Curi; Sandra Coccuzzo Sampaio (Hindawi Limited, 2016)
We investigated the effects of Crotoxin (CTX), the main toxin of South American rattlesnake (Crotalus durissus terrificus) venom, on Walker 256 tumor growth, the pain symptoms associated (hyperalgesia and allodynia), and participation of endogenous lipoxin A4. Treatment with CTX (s.c.), daily, for 5 days reduced tumor growth at the 5th day after injection of Walker 256 carcinoma cells into the plantar surface of adult rat hind paw. This observation was associated with inhibition of new blood vessel formation and decrease in blood vessel diameter. The treatment with CTX raised plasma concentrations of lipoxin A4 and its natural analogue 15-epi-LXA4, an effect mediated by formyl peptide receptors (FPRs). In fact, the treatment with Boc-2, an inhibitor of FPRs, abolished the increase in plasma levels of these mediators triggered by CTX. The blockage of these receptors also abolished the inhibitory action of CTX on tumor growth and blood vessel formation and the decrease in blood vessel diameter. Together, the results herein presented demonstrate that CTX increases plasma concentrations of lipoxin A4 and 15-epi-LXA4, which might inhibit both tumor growth and formation of new vessels via FPRs.